2002
DOI: 10.1016/s0176-2680(02)00083-6
|View full text |Cite
|
Sign up to set email alerts
|

Wages and the bargaining regime in a corporatist setting: the Netherlands

Abstract: Wages and the bargaining regime in a corporatist setting: The Netherlands Hartog, J.; Leuven, E.; Teulings, C.N. Link to publicationCitation for published version (APA): Hartog, J., Leuven, E., & Teulings, C. (1997). Wages and the bargaining regime in a corporatist setting: The Netherlands. (Discussion Papers; No. 1706). Amsterdam: University of Amsterdam, Centre for Economic Policy Research. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 13 publications
6
55
1
6
Order By: Relevance
“…In the Netherlands, the wages of female workers are 10% lower than those of male workers among workers covered by extended contracts, but the gender difference in earnings is 14% among workers who were not covered by a collective contract [7]. Similarly, in Spain the gender wage gap among workers covered by country-or sector-level contracts is lowest at the bottom of the wage distribution, where actual wages are closest to bargained wages [8].…”
Section: Benefits Of Collective Contract Extensions: Impacts On Wage mentioning
confidence: 97%
“…In the Netherlands, the wages of female workers are 10% lower than those of male workers among workers covered by extended contracts, but the gender difference in earnings is 14% among workers who were not covered by a collective contract [7]. Similarly, in Spain the gender wage gap among workers covered by country-or sector-level contracts is lowest at the bottom of the wage distribution, where actual wages are closest to bargained wages [8].…”
Section: Benefits Of Collective Contract Extensions: Impacts On Wage mentioning
confidence: 97%
“…It is important to note that the questions addressed here go beyond that of the impacts of trade union membership on firm-level performance and inequality as, due the nature of wage bargaining arrangements in Ireland, and continental Europe more generally, the proportion of workers covered by collective bargaining regimes far exceeds the proportion who are members of trade unions (Hartog, 2002). While collective wage bargaining processes will be the primary channel through which trade unions impact wage levels, this is not to say that there are no additional influences deriving from firm trade union density.…”
Section: Introductionmentioning
confidence: 99%
“…Teulings and Hartog (1998) claim that more centralized wagesetting systems can be efficiency enhancing. For Portugal, Hartog, Pereira, and Vieira (2002) found that the level at which bargaining takes place has a significant impact on the wage distribution and on the returns to worker and firm attributes, and evidence on The Netherlands points in the same direction (Hartog, Leuven, and Teulings 2002). The impact of collective bargaining on the wage structure, wage rigidity, and labor market performance is, therefore, not clear-cut.…”
Section: Introductionmentioning
confidence: 99%